Organic field-effect transistors with low-temperature curable high-k hybrid gate dielectrics - Yiwen Liu; Yongfei Wang; Xiao Li; Zhizhi Hu (Materials Research Express, 2022)
We report a low-voltage-operated organic field-effect transistor that uses a hybrid gate insulator that has a high dielectric constant k . The gate insulator consists of a high- k polymer cyanoetylated pullulan (CEP) that can be efficiently cross-linked by glycidoxypropyltrimethoxysilane (GOPTMS) at low temperature (∼110 °C). The very low curing temperature is below the glass transition temperature T _g of conventional plastic substrates for plastic electronics, and is therefore compatible with many plastic substrates for plastic electronics. The cross-linking is very efficient in that only 1/10 (w:w) GOPTMS: CEP produced densely cross-linked thin films with a smooth surface, good insulating property, high capacitance density and high k . The devices functioned at low voltage, and exhibited charge carrier mobility ∼1.83 cm ^2 V ^−1 s ^−1 , and steep substheshold swing ∼88 mV dec ^−1 . These results imply that high quality polymer gate insulators are achievable at low temperature with a very small fraction of blended crosslinking agents; this characteristic offers a method to achieve portable all-plastic flexible electronics that function at low voltage.